2022
DOI: 10.3390/cryst12030335
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on High-Entropy Films Deposited by Magnetron Sputtering

Abstract: High-entropy films (HEFs) are of considerable interest in surface engineering applications due to their superior properties, such as good corrosion resistance, good thermal stability and excellent high temperature oxidation. Recently, the scientific community has seen an increasing development of the multicomponent coatings, improving their properties compared to conventional films. Technically, different strategies have been exploited to fabricate HEFs. Magnetron-sputtered HEFs have made significant advanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Finally, possibly the most important output of the current work for industrial applications is the demonstration of the ability of reactive HiTUS to produce multicomponent coatings with mechanical properties equal to those in a similar arc and DCMS metallic and nitride coating systems [ 9 , 10 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 47 , 48 , 49 , 50 , 51 ] without a feedback control of target poisoning. The structures of the studied coatings, despite variations and deviations from equiatomic concentrations of TM elements at different scales, corresponded to homogeneous solid solutions regardless of the amount of nitrogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, possibly the most important output of the current work for industrial applications is the demonstration of the ability of reactive HiTUS to produce multicomponent coatings with mechanical properties equal to those in a similar arc and DCMS metallic and nitride coating systems [ 9 , 10 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 47 , 48 , 49 , 50 , 51 ] without a feedback control of target poisoning. The structures of the studied coatings, despite variations and deviations from equiatomic concentrations of TM elements at different scales, corresponded to homogeneous solid solutions regardless of the amount of nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The recent reviews on high entropy ceramic coatings can be found in [ 12 , 16 , 17 ]. Probably the first multicomponent high entropy-like nitride coatings were deposited in 2004 from FeCoNiCrCuAl (Mn) targets by reactive DC magnetron sputtering (DCMS) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…TiN belongs to the category of transition metal nitrides and possesses outstanding physical and mechanical properties, along with considerably high resistance to oxidation and corrosion. Due to these exceptional characteristics, TiN-based thin films are utilized in various applications such as wear-resistant coatings on cutting tools [1], microelectronics applications on semiconductors and interconnectors [2], corrosionresistant coating at acidic ambient [3], oxidationresistant coating for high-temperature applications [4]. TiN thin film can be synthesized through various techniques such as laser ablation [5], thermal evaporation, Chemical Vapor Deposition (CVD) [6], Cathodic Arc Evaporation (CAE) [7], ion beam-assisted Physical Vapor Deposition (IBPVD) [8] and sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…High-entropy films (HEFs), which are cost-effective, have also been investigated [6][7][8][9][10][11][12][13] and have revealed interesting Mohamed El Garah and Driss Soubane have equal contribution.…”
Section: Introductionmentioning
confidence: 99%